Question
upstudy study bank question image url

Solve the following inequality. \[ (x+4)(x+9)(5-x)<0 \] Write your answer as an interval or union of intervals. If there is no real solution, click on "No solution".

Ask by Robbins Vaughn. in the United States
Nov 11,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x \in (-9,-4) \cup (5,+\infty) \).

Solution

Solve the equation \( (x+4)(x+9)(5-x)<0 \). Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(\left(x+4\right)\left(x+9\right)\left(5-x\right)<0\) - step1: Rewrite the expression: \(\left(x+4\right)\left(x+9\right)\left(5-x\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x+4=0\\&x+9=0\\&5-x=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=-4\\&x=-9\\&x=5\end{align}\) - step4: Determine the test intervals: \(\begin{align}&x<-9\\&-95\end{align}\) - step5: Choose a value: \(\begin{align}&x_{1}=-10\\&x_{2}=-7\\&x_{3}=1\\&x_{4}=6\end{align}\) - step6: Test the chosen value: \(\begin{align}&x<-9\textrm{ }\textrm{is not a solution}\\&-95\textrm{ }\textrm{is the solution}\end{align}\) - step7: The final solution is \(x \in \left(-9,-4\right)\cup \left(5,+\infty\right):\) \(x \in \left(-9,-4\right)\cup \left(5,+\infty\right)\) The solution to the inequality \((x+4)(x+9)(5-x)<0\) is \(x \in (-9,-4) \cup (5,+\infty)\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the inequality \((x+4)(x+9)(5-x) < 0\), we first find the points where the expression equals zero: 1. \(x + 4 = 0 \implies x = -4\) 2. \(x + 9 = 0 \implies x = -9\) 3. \(5 - x = 0 \implies x = 5\) This gives us three critical points: \(-9\), \(-4\), and \(5\). We will use these points to test the sign of the expression in the intervals they divide the number line into: 1. **Interval** \((-∞, -9)\): Choose \(x = -10\) \(((-10 + 4)((-10 + 9)(5 - (-10)) = (-6)(-1)(15) > 0\) 2. **Interval** \((-9, -4)\): Choose \(x = -6\) \(((-6 + 4)((-6 + 9)(5 - (-6)) = (-2)(3)(11) < 0\) 3. **Interval** \((-4, 5)\): Choose \(x = 0\) \(((0 + 4)((0 + 9)(5 - 0)) = (4)(9)(5) > 0\) 4. **Interval** \((5, ∞)\): Choose \(x = 6\) \(((6 + 4)((6 + 9)(5 - 6)) = (10)(15)(-1) < 0\) Now, let's compile the intervals where the product is negative: - The product is negative in \((-9, -4)\) and \((5, ∞)\). Thus, the solution to the inequality \((x+4)(x+9)(5-x)<0\) is: \[ (-9, -4) \cup (5, \infty) \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy